Development of Sattankulam heavy mineral sands, Tamilnadu, India by Tata Steel - Ch. V. G. K. Murty; S. Asokan; D. Rathod (Society for Mining, Metallurgy & Exploration, 2005)
Tata Steel, a steel arm of Tata Group, is Asia's first and India's largest integrated private sector steel company. Tata Steel’s turnover in fiscal 2004-05 was nearly US$ 3.25 billion. As part of its vision to grow in related industries, Tata Steel is poised to enter the Titania businesses in the Indian state of Tamil Nadu. The Titania project will involve mining, separation of ilmenite & other co-minerals, beneficiation of ilmenite to synthetic Rutile and further maximum value addition to Titanium metal. This paper outlines the journey from the concept to current findings of the Bankable Feasibility Study in developing Sattankulam Heavy Mineral Sands Deposits in the State of Tamil Nadu, India by Tata Steel.